EFFECT OF GLYCINE BETAINE, SALICYLIC ACID, AND POTASSIUM ON DIFFERENT TRAITS OF SOYBEAN CROP UNDER WATER STRESS - Kassar, Moayad; Ahmed, Shatha (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to investigate the role of glycine betaine, salicylic acid, and potassium in supporting soybean plants grown under water stress. A field experiment was conducted at Wasit Governorate during the autumn seasons of 2022 and 2023.  randomized complete block design (RCBD) with split plot using arrangement and three replications, conditions treatments of water depletion levels of 30%, 45%, and 60%. Water treatments were allocated to the main plots, While the treatments, which included A0 (control treatment) of dry seeds and distilled water spray, A1 (50 mmol L-1 Glycine betaine seed soaking), A2 (300 mg L-1 salicylic acid spray), A3 (50 m mol L-1 Glycine betaine seed soaking and 300 mg L-1 salicylic acid spray), A4 (7.2 g L-1 potassium spray), A5 (50 mmol L-1 Glycine betaine seed soaking and 7.2 g L-1 potassium spray), and A6 (combination of the above treatments), were assigned to the subplots. The results indicated non significant differences among irrigation treatments at 30% and 45% water depletion in plant height, leaf area, chlorophyll content in the second season, plant dry weight, membrane stability, potassium content and seed yield in both seasons. However, plants subjected to irrigation at 60% water depletion showed higher average proline content (2.7 and 2.8) µmol g-1.The interaction between plant support treatments and irrigation was statistically significant in plant height, leaf area, chlorophyll content, and plant dry weight.